Penatalaksanaan Fisioterapi pada Kasus Frozen Shoulder : a Case Report - Andhika Fatir Ath-Thariq; Isnaini Herawati; Warih Sri Widodo (Jurnal Medika Nusantara, 2025)
Background: Frozen shoulder also known as adhesive capsulitis, is a common shoulder disorder that manifests as pain and progressive loss of shoulder motion. Frozen shoulder can be primary or secondary, which refers to whether the condition occurs spontaneously, without known cause or trauma to primary frozen shoulder, or whether it is associated with trauma, surgery or other pathologies, such as secondary frozen shoulder subacromial pain. Method: This study design used a case report method which observed one patient with a case of left frozen shoulder. The observation location was at Panembahan Senopati Bantul Hospital. Examination using the Numeric Rating Scale (NRS) for pain examination, Manual Muscle Testing (MMT) for muscle strength examination, goniometer for joint range of motion (LGS) examination, palpation for spasm examination, Shoulder Pain and Disability Index (SPADI) for functional activity evaluation. Results: This study showed that physiotherapy treatment for 3 meetings increased joint range of motion, increased muscle strength, decreased spasm and reduced pain in patients with frozen shoulder. Conclusion: Infrared, TENS, Massage, Active resisted exercise and SPADI are effective in treating frozen shoulder cases.